Pengaruh Faktor Internal dan Makroekonomi Terhadap Risiko Kredit Pada Bank BUSN Devisa Periode 2012-2016 - AMELIA ALFIN, NENIA; HARTONO, ULIL (Jurnal Ilmu Manajemen (JIM), 2018)
Abstract Bank holdsan important role in financial sector of a country. It is because bank is an institution which function as intermediation. This research is aimed to find out the influence of Return on Assets (ROA), Net Interest Margins (NIM), Loan to Deposit Ratio (LDR), Capital Aduquacy Ratio (CAR), Inflation, Exchange Rate, and Gross Domestic Product to credit risk (GDP). Credit risk is proxied using NPL. This research uses quantitative approach and secondary data which taken from Financial Report published on official website of each bank. The population used in this research is BUSN bank Devisa which enlist on OJK with the total of 51 banks. The sample in this research amounted to 36 banks which obtained based on purposive sampling method. The analysis method uses is multiple linear regression. The result shows that ROA, NIM, CAR, and Exchange Rate are affecting credit risk. Meanwhile, LDR, Inflation, and GDP have no effect on credit risk. LDR does not affect credit risk because the amount of credit will not increase the risk of non performing loans because banks are more selective in observing prospective borrowers before giving credit. Inflation does not affect credit risk because inflation is still categorized low so it does not affect the NPL. GDP has no effect on credit risk because the increase in NPL is not caused by the level of GDP but is caused by other factors